HIV testing rates, prevalence, and knowledge among outpatients in Durban, South Africa: Time trends over four years - Ramirez-Avila, Lynn; Regan, Susan; Chetty, Senica; Giddy, Janet; Ross, Douglas; Katz, Jeffrey N; Freedberg, Kenneth A; Losina, Elena; Walensky, Rochelle P; Bassett, Ingrid V (International journal of STD & AIDS, 2015)
The HIV public health messages in South Africa have increased. Our objective was to evaluate changes over time in HIV testing behaviour, prevalence and knowledge. We prospectively enrolled adults (≥18 years) prior to HIV testing at one urban and one peri-urban outpatient department in Durban, South Africa. A baseline questionnaire administered before testing included the number of prior HIV tests and four knowledge items. We used test results to estimate previously undiagnosed HIV prevalence among those tested. We assessed linear trends over enrollment. From November 2006 to August 2010, 5229 subjects enrolled and 4877 (93%) were HIV tested and had results available. Subjects reporting prior testing over time increased, from 13% in study year 1 to 42% in year 4 (linear trend p < 0.001). The HIV prevalence among those tested declined steadily and significantly over time, from 64% of enrollees in study year 1 to 39% in the final year (linear trend p < 0.001). The percentage of subjects who recognised that medicine can help people with HIV live longer increased from 80% in study year 1 to 96% in study year 4. Rates of HIV testing have increased and prevalence among those tested has decreased in outpatients in Durban, South Africa.